EXPLORING EFL STUDENTS’ EXPERIENCES AND PERCEPTIONS OF USING ELSA SPEAK AS A TOOL FOR ENHANCING SPEAKING SKILLS THROUGH INDEPENDENT LEARNING - Dzurrotun Nasicha; Nur Chakim (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This qualitative phenomenological study investigates the perceptions and experiences of EFL vocational high school students in using the ELSA Speak application to improve their speaking skills. The research involved 25 tenth-grade students from a vocational school in Mojokerto, East Java, Indonesia. To collect data, questionnaires and interviews are employed. The findings indicate that ELSA Speak positively influenced students’ motivation, self-confidence, and pronunciation accuracy, largely due to its instant feedback and supportive, non-judgmental environment. Moreover, students appreciated the app's flexibility and ease of integration into their daily routines, which enabled them to engage in self-paced learning beyond the constraints of traditional classrooms. Nonetheless, they also encountered challenges such as speech recognition inaccuracies, reliance on internet connectivity, and subscription-related limitations. While students found the app effective for improving technical aspects of speaking, they viewed it as a complementary resource rather than a replacement for classroom interaction. The study recommends integrating ELSA Speak into the language learning curriculum for focused skill practice, while also addressing technical and accessibility issues to enhance its effectiveness.